Analisis Keuntungan Usaha Pisang Ijo sebagai Diversifikasi Pangan Olahan Pisang Manis di Kabupaten Konawe: (Studi Kasus Usaha Kuliner Bapak Ashar) - Novita Ramadani; Muhammad Adwan (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2024)
This study aims to determine the costs, revenues, and profits of Mr. Ashar's Es Pisang Ijo business in Unaaha City. Analysis of the Es Pisang Ijo business is important for producers to know the state of the business, especially from the financial side, so that it can be used as a contribution of thought, evaluation material, and consideration in making decisions related to the progress of Mr. Ashar's Es Pisang Ijo business. This study uses a case study research type. Data collection techniques Data collection techniques used are: Primary data and secondary data. Sampling technique The withdrawal of respondents in this study was carried out purposively or intentionally, at Mr. Ashar's Es Pisang Ijo Culinary business in Unaaha City, Konawe Regency. The total cost of Mr. Ashar's Es Iisang Ijo Business in one production process with raw materials of 4 combs of sweet bananas produces an output of 65 cups of Es Pisang Ijo in one production process, with a total cost of Rp. 421,500.00 and the income obtained in one production process is Rp 975,000.00, thus obtaining a profit of Rp 553,500.00. The R/C value produced by Mr. Ashar's Es Pisang Ijo business is 1.76.